The Contribution of Learning Motivation and Parents’ Socio-Economy towards Students’ Learning Outcomes through Learning Independence - Putu Shinta Kusumaningtyas; Desak Putu Parmiti; Komang Setemen (Universitas Pendidikan Ganesha, 2023)
The issue about online learning above cause a serious problem in the learning process conducted in Indonesia during covid-19 pandemic. It is stated that there is a decrease towards students’ learning outcomes during online learning. This study aims to analyze the contribution of students’ learning motivation and parents’ socio-economy towards students’ learning outcomes through learning independence. The study population was 2716 students. The research sample was 350 students. Research using path analysis techniques. The results of the study are: there is a positive contribution between learning motivation to economic learning outcomes with a contribution of 13% to economic learning outcomes. There is a direct influence between socioeconomic conditions on economic learning outcomes with a contribution of 30% to economic learning outcomes. There is an influence between learning independence on economic learning outcomes with a contribution of 22% to economic learning outcomes. There is an influence between learning motivation on learning independence with a contribution of 22% to learning independence. There is an influence between parents' socioeconomic conditions on learning independence with a contribution of 13% to learning independence. There is an indirect influence between learning motivation on economic learning outcomes through learning independence by 5%. There is an indirect influence between learning motivation on economic learning outcomes through learning independence by 3%. Can be concluded that students’ learning motivation and parents’ socio-economy during online learning plays an important role in influencing students’ learning outcomes.